The Effect of Corporate Social Responsibility and Tourism Development on Regional Development in Berau Regency - Suharto, Rahcmad; Hasid, Zamruddin; Ilyas, Laode; Mahardika, Swadia (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The aim of the research is to test the truth of regional development theories, namely firm location theory and new economic geography theory, as well as functional development theory, with the research object being the PT company. Berau Coal in Berau district, East Kalimantan province. It recommends the results of research, namely the corporate social responsibility program and tourism development, towards regional development in Berau Regency, East Kalimantan Province. The method used in this research is a quantitative research method. Multivariate analysis is used in analyzing research, involving variables in a number greater than or equal to three variables. WarpPLS is mutivariate-based and can analyze structural equation modeling (SEM). The results of the research show that PT Berau Coal's corporate social responsibility (CSR) program has a positive and significant effect on regional development. The tourism development that has been carried out has been proven to have a positive and significant effect on regional financial independence. The existence of the tourism industry in Berau district has increased regional development. Regional financial independence will become more independent if the contribution of regional original income (PAD) to funding regional development is greater.